Does real maximal claudication distance correspond with patients estimation? - Spannbauer, Anna; Jaworek, Jolanta; Chwała, Maciej; Mika, Piotr (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2009)
Background: What is your pain-free and maximal walking distance? That is a general question when the medical history of a patient with claudication is taken by a vascular surgeon or nurse. The answer to that question is one of the important factors influencing further choice of treatment modality, since a distance shorter than 100 m is considered an indication for surgical treatment. The aim of this study was to compare maximal walking distances reported by patients based on their subjective observations with objective data from the corridor test. Material and methods: A group of 35 patients with peripheral arterial disease and intermittent claudication (II Fontaine) participated in this study. The walking distance was assessed based on patients’ reports and corridor test performed with stable speed of 100 steps/min and physiotherapist’s assistance. Results: There was a lack of relationship between declared walking distances and results from the corridor test. The shorter distance was reported by 80% and longer distance was reported by 6% of patients as compared to corridor test results. Only five patients (14%) answered similarly to verified distance. Conclusions: 1. The patients reported that walking distance is generally lower than that obtained from the corridor test. 2. Information obtained from a patient with claudication should be verified objectively. 3. The corridor test is a useful tool of walking distance examination and may be helpful in making a decision concerning the patient’s future treatment.